A Comparative Analysis of Ring Signature Schemes for Anonymous Feedback Systems (International Journal of Scientific Research in Science and Technology, 2025)
With the rise of the demand for secure and unidentifiable communication, feedback systems in academic and organizational settings face extreme difficulties in terms of user privacy and feedback attestation. Current approaches, particularly anonymized surveys, rely on third-party frameworks which come with high risks of data leakage and impersonation. The goal of this study is to develop an anonymous feedback system using cryptographic ring signatures that guarantees user anonymity while validating feedback authenticity. The study focuses on the comparison of three cryptographic algorithms: RSA, ECC, and LSAG, to find the most effective and secure solution for such systems. This study incorporated the design of a feedback system with ring signatures that enabled the anonymization of responses. To provide an interface that allows smooth interaction with users, a frontend was developed and combined with the backend where key cryptographic algorithms (RSA, ECC, LSAG) were implemented and evaluated based on effectiveness, computational requirements, and key dimensions. An excellent option for safe anonymous feedback systems is the ECC-based ring signature technique, which showed excellent performance. Future research could examine how the technology can be applied in real-world settings and integrated with other privacy-enhancing technologies
Keywords: Anonymous Feedback System; ECC; Ring Signature; Privacy Preservation; Digital Signature